2010
DOI: 10.1577/h09-010.1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Aquaflor (50% Florfenicol) to Control Mortality Associated with Streptococcus iniae in Freshwater‐Reared Subadult Sunshine Bass

Abstract: We conducted a field trial to evaluate the effectiveness of Aquaflor (50% florfenicol) for controlling mortality associated with Streptococcus iniae in freshwater-reared subadult sunshine bass (female white bass Morone chrysops X male striped bass M. saxatilis). Bacterial samples collected from moribund fish representing a reference population were presumptively identified microbiologically and were later confirmed to be S. iniae by biochemical characterization and polymerase chain reaction. The trial comprise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 42 publications
0
18
0
2
Order By: Relevance
“…Because of its high potency and because it is not used in human medicine, florfenicol has become an important veterinary therapeutic drug, especially when administered in feed. Florfenicol can control mortality caused by furunculosis in Atlantic Salmon Salmo salar (Nordmo et al 1994;Samuelsen et al 1998), pseudotuberculosis in Yellowtail (buri) Seriola quinqueradiate (Yasunaga and Yasumoto 1988), columnaris in Largemouth Bass Micropterus salmoides, and Bluegill Lepomis macrochirus (Matthews et al 2013), and streptococcal disease 517 518 BOWKER ET AL. in sunshine bass (female White Bass Morone chrysops × male Striped Bass M. saxatilis) (Darwish 2007;Bowker et al 2010) and Nile Tilapia Oreochromis niloticus (Gaunt et al 2010). In addition, florfenicol caused no mortalities, changes in fish growth, or clinical changes in Channel Catfish Ictalurus punctatus (Gaikowski et al 2003) when fed for 20 d at doses up to 34.9 mg florfenicol·kg fish −1 ·d −1 or in sunshine bass (Straus et al 2012) when fed for 20 d at doses up to 75 mg florfenicol·kg fish −1 ·d −1 .…”
mentioning
confidence: 99%
“…Because of its high potency and because it is not used in human medicine, florfenicol has become an important veterinary therapeutic drug, especially when administered in feed. Florfenicol can control mortality caused by furunculosis in Atlantic Salmon Salmo salar (Nordmo et al 1994;Samuelsen et al 1998), pseudotuberculosis in Yellowtail (buri) Seriola quinqueradiate (Yasunaga and Yasumoto 1988), columnaris in Largemouth Bass Micropterus salmoides, and Bluegill Lepomis macrochirus (Matthews et al 2013), and streptococcal disease 517 518 BOWKER ET AL. in sunshine bass (female White Bass Morone chrysops × male Striped Bass M. saxatilis) (Darwish 2007;Bowker et al 2010) and Nile Tilapia Oreochromis niloticus (Gaunt et al 2010). In addition, florfenicol caused no mortalities, changes in fish growth, or clinical changes in Channel Catfish Ictalurus punctatus (Gaikowski et al 2003) when fed for 20 d at doses up to 34.9 mg florfenicol·kg fish −1 ·d −1 or in sunshine bass (Straus et al 2012) when fed for 20 d at doses up to 75 mg florfenicol·kg fish −1 ·d −1 .…”
mentioning
confidence: 99%
“…Perera et al (1997) reported higher mortality in Nile Tilapia × Blue Tilapia hybrids when fish were maintained at 20 • C than when maintained at 15, 25, 30 or 35 • C. The dose confirmation study reported by Gaunt et al (2010) was closest in temperature (27 • C) to our trial (about 29 • C), and mortality of challenged, unmedicated tilapia (20.5%) in that portion of their study was closest to our findings. Darwish (2007) and Bowker et al (2010) reported that FFC-medicated feed significantly increased survival of sunshine bass (female White Bass Morone chrysops × male Striped Bass M. saxatilis) relative to fish fed nonmedicated control fish following laboratory challenge with S. iniae or during a natural outbreak of streptococcosis. In both studies with sunshine bass mortality was substantial (>50%) for nonmedicated fish.…”
Section: Discussionmentioning
confidence: 99%
“…Florfenicol was found to be effective in controlling mortality due to S. iniae in laboratory-challenged tilapia Oreochromis sp. (Darwish 2010) and under laboratory-challenge (Darwish 2007) and field conditions (Bowker et al 2010) with hybrids of Striped Bass Morone saxatilis × White Bass M. chrysops fed FFC-medicated feed at a rate sufficient to administer a FFC dose of 10 mg/kg BW per day for 10 consecutive days. Gaunt et al (2010) evaluated the efficacy of florfenicol administered to tilapia in a controlled tank study challenged with S. iniae at daily dose rates of 5, 10 and 15 mg/kg for 10 consecutive days; they selected the dose rate of 15 mg/kg BW for development.…”
mentioning
confidence: 99%
“…Others have reported that florfenicol treatments reduced mortality in catfish caused by ESC associated with Edwardsiella ictaluri (Gaunt et al , 2004, in Atlantic Salmon Salmo solar caused by furunculosis associated with Aeromonas salmonicida (Samuelsen et al 1998), and in sunshine bass (female White Bass Morone chrysops × male Striped Bass M. saxatilis) associated with Streptococcus iniae (Darwish 2007;Bowker et al 2010). Bowker et al (2010) reported that the analytically verified florfenicol dose administered was 8.3 mg/kg body weight per day. Regardless, these authors reported that mean percent cumulative mortality in treated tanks (19%) was significantly different from that in control tanks (52%).…”
Section: Discussionmentioning
confidence: 99%
“…Leading up to approval in April 2012, public and private aquaculture groups in the USA sought to expand the approved Aquaflor label to include additional freshwater-reared finfish species and pathogens susceptible to florfenicol. Florfenicol has been shown to be efficacious against a number of fish pathogens, including Aeromonas salmonicida and Vibrio salmonicida (Fukui et al 1987;Inglis and Richards 1991;Nordmo et al 1998;Samuelsen et al 1998;Bruun et al 2000;Schmidt et al 2001), Edwardsiella ictaluri (McGinnis et al 2003), F. columnare (Gaunt et al 2010b), and Streptococcus iniae (Bowker et al 2010).…”
mentioning
confidence: 99%